2021
DOI: 10.3390/molecules26164968
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of MIF in the Secretion of IL-25, IL-31, and IL-33 from PBMC of Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune inflammatory joint disease with complex pathogenesis associated with cytokine dysregulation. Macrophage migration inhibitory factor (MIF) plays a role in systemic inflammation and joint destruction in RA and could be associated with the secretion of other immune-modulatory cytokines such as IL-25, IL-31, and IL-33. For the above, our main aim was to evaluate the IL-25, IL-31, and IL-33 secretion from recombinant human MIF (rhMIF)-stimulated peripheral blood mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…In 2019, Zhu et al identified an overexpression of miR-99b-5p in RA patients which was responsible for promoting lymphocyte proliferation and activation, suppression of lymphocyte T apoptosis and increase in cytokine production [86]. Moreover, expression patterns and cytokine secretion dynamics during RA are constantly researched, as shown in Garcia-Arellano et al's 2021 paper in which researchers identified a novel role of the macrophage migration inhibitory factor (MIF) in IL-25, IL-31 and IL-33 secretion [87]. Therapy and treatment of RA is an increasingly important field of research tasked with the investigation of novel drugs as well as their potential targets.…”
Section: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…In 2019, Zhu et al identified an overexpression of miR-99b-5p in RA patients which was responsible for promoting lymphocyte proliferation and activation, suppression of lymphocyte T apoptosis and increase in cytokine production [86]. Moreover, expression patterns and cytokine secretion dynamics during RA are constantly researched, as shown in Garcia-Arellano et al's 2021 paper in which researchers identified a novel role of the macrophage migration inhibitory factor (MIF) in IL-25, IL-31 and IL-33 secretion [87]. Therapy and treatment of RA is an increasingly important field of research tasked with the investigation of novel drugs as well as their potential targets.…”
Section: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…Furthermore, macrophages respond to pro-inflammatory stimuli by secreting IL-33. The synovium of RA patients is associated with a greater presence of macrophage migration inhibitory factor (MIF) [104], a pro-inflammatory molecule that induces the expression of IL-33 in PBMC obtained from RA patients [105]. Moreover, IL-33 affects the behavior of dendritic cells, whose greater presence is found in the synovial fluids of RA patients [106].…”
Section: Interleukin-33mentioning
confidence: 99%